Respuesta inmunológica en porcinos experimentalmente infectados con larvas de Toxocara cati - Sierra, María Florencia (2018)
Human toxocariasis is a disease that occurs as a result of the presence of Toxocara canis and T. cati larvae in different tissues. T. cati is the most prevalent endoparasite found in domestic cats. For many years only T. canis was considered as the most important, perhaps the only agent of human toxocariasis and the role as a zoonotic agent of T. cati was underestimated.\nFemale worms of T. cati eliminate unsegmented eggs through the feces of the parasitized cats. The eggs need to maturate in the environment to reach its infecting stage (L3). The main source of infection for the definitive and paratenic hosts, including the humans, is through the eggs present in the environment. Currently, T. cati is frequently found in the environment and it represents a risk to public health.\nHuman toxocariasis includes the recognized syndromes Larva Migrans Visceral, Larva Migrans Ocular, Neurotoxocariasis and Covert Toxocariasis. Definitive diagnosis is only accessible through visualization of larvae in different tissues by biopsy, but it is an invasive, and low practical method. Nowadays, indirect techniques are used to detect the immune response triggered by the presence of the parasite. An ELISA detecting specific IgG antibodies against the "excretory-secretory" antigens of Toxocara (TES) is considered the worldwide reference test. It has a high sensitivity but low specificity. In countries like Argentina where polyparasitism exist this is a disadvantage due to the presence of cross-reactions mainly with other helminths. Development of Western Blot technique that allows the visualization of specific bands of Toxocara spp. infection has reduced false positive results and is used as confirmatory test.\nIn vivo experimental models allows to study processes that are complex. Because of their physiological and immunological similarities with humans, pigs represent a good experimental model to study Toxocara cati infection and the development of the specific humoral immune response. At present there are no studies performed on experimentally infected pigs with T. cati eggs that study the immune response and its evolution over time.\nAn experimental study was conducted in porcine with a single dose of infective eggs of Toxocara cati. The specific humoral immune response against the TES antigen was studied. TES antigen was obtained from the culture of larvae from eggs found in feces of naturally infected cats. The evolution of specific humoral immune response in the acute and chronic stages of infection was evaluated. ELISA and Western Blot techniques were used to determine specific IgM and IgG antibodies. Both techniques are those used for the diagnosis of human toxocariasis ELISA and Western Blot techniques detected the development of an immune response against T. cati infection in pigs. It was different depending on the time of evolution of the infection. Significant differences in the kinetic behavior of both immunoglobulins isotype studied at different times were observed during the acute stage through the ELISA technique. No statistical differences were detected during the chronic stage of infection where both immunoglobulins presented high and stable levels.\nWestern Blot technique allowed the visualization of a different immunogenic band pattern between the acute and chronic stages of T. cati infection. For both immunoglobulins, higher molecular weight bands appeared from the beginning of the infection in the acute stage. The chronic stage of infection was characterized by lower molecular weight bands. Greater differences were observed in the chronic stage between the specific IgM and IgG antibodies. Specific IgG presented the more immunogenic bands. Specific IgM antibody only shows a band of approximately 31 kDa.\nPigs have been proposed as a model of excellence for the study of the infection by Toxocara spp. in paratenic hosts like humans. In consequence, results obtained during this thesis provide information that could be useful to study the humoral immune response in humans and thus improve the diagnosis of human toxocariasis. In addition, they provide information on the response of specific IgM antibodies against T. cati infection, about which little is known.